The Consequences of Stigma for Knowledge Production: Sheep Producers' Attitudes to Footrot Diagnostics and Control in Australia - Best, Nickala; Menéndez, Ramón; Rawlin, Grant; Suter, Robert; Rodoni, Brendan; Beddoe, Travis (Frontiers in Veterinary Science, 2020)
In Australia, there has been a perceived stigma surrounding the disease of footrot in sheep for many years. There is documented confusion from producers around clinical disease of footrot, and anecdotally, knowledge of what tools are available for the diagnosis and management of footrot. When discussing footrot, embarrassment and denial is often encountered due to the perceived image of having footrot. The disease can be debilitating, both on the sheep’s welfare and the producer’s wellbeing, as it is a very difficult disease to manage and eradicate. Gaining an understanding of producer perceptions of the disease will help ensure any future actions for management and control are in-line with those identified by producers. A combination of a web-based, and manually distributed surveys of 45 sheep producers was conducted. This included closed- and open-ended questions, multi check box, and Likert scales. Responses were quantified by descriptive statistics and a thematic analysis conducted of short answers. The results of this survey indicate satisfaction with footrot diagnostics is low, while satisfaction with treatment methods is high. There was also a poor general understanding of footrot as a disease, and a general distrust in peers when it comes to correct management of this disease. This research addresses a gap in the knowledge about sheep producers’ attitudes to footrot, providing recommendations such as simplifying the diagnostic message and changing the wording used for footrot, to encourage a culture of trust for diagnosing and managing the disease.